2011
DOI: 10.1128/jb.01350-10
|View full text |Cite
|
Sign up to set email alerts
|

YjbH-Enhanced Proteolysis of Spx by ClpXP in Bacillus subtilis Is Inhibited by the Small Protein YirB (YuzO)

Abstract: The Spx protein of Bacillus subtilis is a global regulator of the oxidative stress response. Spx concentration is controlled at the level of proteolysis by the ATP-dependent protease ClpXP and a substrate-binding protein, YjbH, which interacts with Spx. A yeast two-hybrid screen was carried out using yjbH as bait to uncover additional substrates or regulators of YjbH activity. Of the several genes identified in the screen, one encoded a small protein, YirB (YuzO), which elevated Spx concentration and activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 52 publications
1
29
2
Order By: Relevance
“…YjbH bears a His-Cys-rich region on the N terminus which is important for Zn metal binding and for enhancement of proteolysis of Spx by ClpXP (Garg et al, 2009 (Kommineni et al, 2011). However, no Spx-related phenotype has been uncovered in the yirB deletion mutant.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…YjbH bears a His-Cys-rich region on the N terminus which is important for Zn metal binding and for enhancement of proteolysis of Spx by ClpXP (Garg et al, 2009 (Kommineni et al, 2011). However, no Spx-related phenotype has been uncovered in the yirB deletion mutant.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies (Garg et al, 2009;Kommineni et al, 2011;Larsson et al, 2007) showed that YjbH acts as a substrate recognition factor to enhance Spx proteolysis by ClpXP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not fully understood how the adaptor activity of YjbH is regulated. However, recently is has been reported that in B. subtilis the 54-amino-acid protein YirB may function as an antiadaptor protein (18). It is suggested that YirB functions by interacting with YjbH, causing a subsequent release of Spx from YjbH (18).…”
mentioning
confidence: 99%